Agricultural Greenhouse Gas Fluxes Under Different Cover Crop Systems - Wang, Yanyu; Saikawa, Eri; Avramov, Alexander; Hill, Nicholas S. (Frontiers in Climate, 2022)
Cultivated lands that support high productivity have the potential to produce a large amount of GHG emissions, including carbon dioxide (CO2), nitrous oxide (N2O), and methane (CH4). Intensive land management practices can stimulate CO2, N2O, and CH4 emissions from the soil. Cover crop establishment is considered as one of the sustainable land management strategies under warm and humid environmental conditions. To better understand how the incorporation of cover crops affect three major GHGs, we compared trace gas fluxes in a no-till maize field over the whole growing season in 2018 in a no cover crop (Tr) system and three cover crop systems: crimson clover (CC), cereal rye (CR), and living mulch (LM) using white clover. In 2019, we further explored potential differences in the three GHGs between in-row (IR) and between-row (BWR) of maize for LM and Tr systems during the early growing season. Measurements were taken using a cavity ring-down spectroscopy gas analyzer in Watkinsville, GA. In 2018, the highest CO2 flux (7.00 μmol m−2 s−1) was observed from BWR of maize for LM. The maximum N2O flux observed in LM on June 20th in 2018 was when soil N increase rate was the largest. Soils served as sinks for CH4 and Tr system served as the smallest CH4 sink compared to the other three cover crop systems. For N2O, the highest fluxes were observed from the TrIR plot (4.13 μmol m−2 hr−1) in 2019 with the greatest N inputs. In 2019, we observed a smaller CH4 sink in TrIR (−0.13 μmol m−2 hr−1) compared to TrBWR (−0.67 μmol m−2 hr−1) due potentially to greater NH4+ inhibition effects on CH4 consumption from greater N fertilizer inputs. The net carbon equivalent (CE) from May 23rd to Aug 16th in 2018, taking into account the three GHG fluxes, soil carbon content, and fertilizer, irrigation, and herbicide application, were 32–97, 35–101, 63–139, and 40–106 kg ha−1 yr−1 for CC, CR, LM, and Tr, respectively. LM had the lowest net CE after removing white clover respiration (−16–60 kg ha−1 yr−1). Our results show that implementing different types of cover crop systems and especially the LM system have some potential to mitigate climate change.